Public spending and poverty in Mozambique - Rasmus Heltberg; Kenneth Simler; Finn Tarp (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2001)
Little is known about the extent to which public spending is targeted towards the poor in Mozambique. The objective of the present paper is to assess whether public expenditures on education and health, in particular, are successful at reaching the poorer segments of the Mozambican population. Standard non-behavioural benefit-incidence methodology is applied, combining individual client information from survey data with provincial-level data on the cost of service provision. Most of the public services we are able to measure turn are moderately progressive, although some of the instruments we could not measure are probably less equally distributed. In Mozambique it appears that regional and gender imbalances in health and education are more significant than income-based differences. Nevertheless, increased public expenditures on health and education—such as that related to the HIPC initiative—are likely to have significant poverty reducing effects.
Keywords: H42; H51; H52; O55; F34; 330; government expenditure; poverty and inequality; Mozambique; Armut; Öffentliche Ausgaben; Öffentliche Bildungsausgaben; Gesundheitskosten; Mosambik